THE IMPLEMENTATION OF LAW ON THE PROTECTION OF WITNESSES AND VICTIMS FOR THE LAW EXISTENCE OF PEOPLE IN GORONTALO CITY - Dungga, Weny Almoravid (Journal of Community Research and Service, 2018)
AbstractThe people's need of legal certainty is the responsibility of all parties to make it happen. Various cases raised in society require the law enforcement agencies to follow up and protect the witnesses and victims. Gorontalo city is inseparable with some legal cases taken place in urban communities that require contributions from law enforcement agencies, including universities. This study focuses on the implementation of law on the protection of witnesses and victims for the law existence to people in Gorontalo city that employed normative juridical method in which it is a law study aimed at finding out the norms and œdas Sollen. The result reveals that the implementation of law on the protection of witnesses and victims to people in Gorontalo city has not been effectively applied as resulted from the empirical factual review. Further, there are five important aspects that determine the existence of witness and victim protection agency, including 1) laws, 2) the witnesses™ and victims™ mental attitude, 3) professional law enforcement officers, 4) community control, 5) electronic media. Keywords: Protection, Witnesses, Victims